The Influence of Satisfaction and Activity of MSMEs at Integrated Business Service Center - Heryatno, Roni; Kusumaningtyas, Ary Wijayati; Pradipto, Chandra (Dinasti Publisher, 2025)
This study examines the influence of facilities and services on Micro, Small, and Medium Enterprises (MSMEs) satisfaction and activity levels at the Integrated Business Service Center in Surakarta. Using a quantitative approach with Structural Equation Modeling-Partial Least Squares (SEM-PLS), data were collected from 100 MSME participants through questionnaires. The research model investigated seven hypotheses examining direct and indirect relationships between facilities, services, satisfaction, and activity levels. Results demonstrate that facilities significantly influence satisfaction (β=0.325, p<0.05) and indirectly affect activity through satisfaction (β=0.114, p<0.05). Services strongly predict both satisfaction (β=0.765, p<0.001) and activity (β=0.833, p<0.001), with satisfaction serving as a mediator (β=0.637, p<0.001). The model explains 86.2% variance in activity and 94.6% in satisfaction, indicating robust predictive power. These findings suggest that improving service quality and facility infrastructure at business incubation centers can enhance MSME engagement and satisfaction, contributing to sustainable business development initiatives